Macrobrachium sbordonii (Decapoda: Palaemonidae), a new stygobitic species of freshwater prawn from Chiapas Mexico - Mejía-Ortíz, Luis M.; Baldari, Fabiola; López-Mejía, Marilú (Zootaxa, 2008)
The fourth stygobitic species of the genus Macrobrachium from caves in America is described. Macrobrachium sbordonii, a new species inhabiting a cave of Chiapas Mexico, is similar to M. villalobosi, M. acheronthium and M. catonium in exhibiting reduced eyes, unpigmentated body and enlargement of ambulatory appendages. It differs from these in length of the first pereiopod and relative proportions of the articles of the second pereiopod, pigmentation degrees on eyes, number of rostral spines, proportions of the scaphocerite, and relative proportions of the carpus and propodus of the first pereiopod. Macrobrachium sbordonii occurs in the inner lake of the Sistema de La Lucha, a cave located near the Chiapas-Oaxaca border, in the Tehuantepec Itsmus Region.